Managing oral bleeding in children with hereditary bleeding disorders: case series and a review of literature - J. O. Eigbobo; F. A. Oredugba; O. O. Orenuga; A. O. Ogunkola; E. O. Temiye (Nigerian Dental Journal)
Bleeding disorders are mostly of genetic or hereditary origin in children. Dental consultations sought by patients with bleeding disorders may follow trauma, dental infections or may be insidious. The present report is on five cases managed at the Paedodontic unit of the Child Dental Health Clinic of the Lagos University Teaching Hospital. The report gives a review of some of the challenges faced in the dental management of patients with hereditary bleeding disorders and the treatment options for the different oral presentations. Four of these patients had haemophilia A and the other had von Williebrand disease. All the patients presented with bleeding gingivae secondary to either physiologic processes of eruption, infective or traumatic dental conditions. The management of the patients was comprehensive with a multidisciplinary approach. The prevention of traumatic and infective dental conditions is an important part of oral health care in individuals with hereditary bleeding disorders. This would reduce the need for treatment and should reduce the number of emergency visits.